Contribution of NAADP to Glutamate-Evoked Changes in Ca2+ Homeostasis in Mouse Hippocampal Neurons - Hermann, Julia; Bender, Melanie; Schumacher, Dagmar; Woo, Marcel S.; Shaposhnykov, Artem; Rosenkranz, Sina C.; Kuryshev, Vladimir; Meier, Chris; Guse, Andreas H.; Friese, Manuel A.; Freichel, Marc; Tsvilovskyy, Volodymyr (Frontiers in Cell and Developmental Biology, 2020)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a second messenger that evokes calcium release from intracellular organelles by the engagement of calcium release channels, including members of the Transient Receptor Potential (TRP) family, such as TRPML1, the (structurally) related Two Pore Channel type 1 (TPC1) and TPC2 channels as well as Ryanodine Receptors type 1 (RYR1) (Guse, 2012). NAADP evokes calcium release from acidic calcium stores of many cell types (Guse, 2012), and NAADP-sensitive Ca2+ stores have been described in hippocampal neurons of the rat (Bak et al., 1999; McGuinness et al., 2007). Glutamate triggers Ca2+-mediated neuronal excitotoxicity in inflammation-induced neurodegenerative pathologies such as Multiple Sclerosis (MS) (Friese et al., 2014), and when applied extracellularly to neurons glutamate can elevate NAADP levels in these cells. Accordingly, glutamate-evoked Ca2+ signals from intracellular organelles were inhibited by preventing organelle acidification (Pandey et al., 2009). Analysis of reported RNA sequencing experiments of cultured hippocampal neurons revealed the abundance of Mcoln1 (encoding TRPML1), Tpcn1 and Tpcn2 (encoding TPC1 and TPC2, respectively) as potential NAADP target channels in these cells. Transcripts encoding Ryr1 were not found in contrast to Ryr2 and Ryr3. To study the contribution of NAADP signaling to glutamate-evoked calcium transients in murine hippocampal neurons we used the NAADP antagonists Ned-19 (Naylor et al., 2009) and BZ194 (Dammermann et al., 2009). Our results show that both NAADP antagonists significantly reduce glutamate-evoked calcium transients. In addition to extracellular glutamate application, we studied synchronized calcium oscillations in the cells of the neuronal cultures evoked by addition of the GABAA receptor antagonist bicuculline. Pretreatment with Ned-19 (50 µM) or BZ194 (100 µM) led to an increase in the frequency of bicuculline-induced calcium oscillations at the cost of calcium transient amplitudes. Interestingly, Ned-19 triggered a rise in intracellular calcium concentrations 25 minutes after bicuculline stimulation, leading to the question whether NAADP acts as a neuroprotective messenger in hippocampal neurons. Taken together, our results are in agreement with the concept that NAADP signaling significantly contributes to glutamate evoked Ca2+-rise in hippocampal neurons and to the amplitude and frequency of synchronized Ca2+ oscillations triggered by spontaneous glutamate release events.